Improving Teachers' Teaching Competence Through Training In Educational Media Creation - Naufal Ahmad Rijalul Alam; Fajar Rachmadhani (Elementaria: Journal of Educational Research, 2025)
This article describes a strategy for improving teachers' competencies through training in the creation of interactive learning media. The research involved 15 teachers from SMA Muhammadiyah Kasihan Bantul as respondents. This evaluative study used pre-test and post-test methods to assess the effectiveness of the training program in creating interactive learning media using the Book Creator and Blooket platforms. The choice of Book Creator and Blooket as learning media was based on their ease of use, which allows for the creation of engaging graphic designs and content that supports interactive and innovative learning. The results of the training activities showed a significant improvement in the teachers' competencies. Before the training, the average knowledge and skills of the teachers in using learning media was only 65%. However, after the workshop, there was a significant increase, with the post-test results showing an average improvement in teacher competencies to 92.5%. Based on these evaluation results, it can be concluded that the training activities were effective in enhancing teachers' competencies, particularly in using interactive media technologies in the learning process. By utilizing platforms like Book Creator, teachers can create more engaging, creative, and student-centered learning materials, thus supporting the achievement of optimal learning outcomes.